2012
DOI: 10.1111/j.1753-4887.2011.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Policies to promote healthy eating in Europe: a structured review of policies and their effectiveness

Abstract: This review provides a classification of public policies to promote healthier eating as well as a structured mapping of existing measures in Europe. Complete coverage of alternative policy types was ensured by complementing the review with a selection of major interventions from outside Europe. Under the auspices of the Seventh Framework Programme's Eatwell Project, funded by the European Commission, researchers from five countries reviewed a representative selection of policy actions based on scientific paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
208
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(219 citation statements)
references
References 44 publications
3
208
0
8
Order By: Relevance
“…Examples of national initiatives aiming for the adoption and maintenance of healthy lifestyle behaviours are physical activity programmes such as the “Exercise on Prescription” (Sørensen, Sørensen, Skovgaard, Bredahl, & Puggaard, 2011) and “Physical Activity on Prescription” (Olsson et al, 2015; Rödjer, Jonsdottir, & Börjesson, 2016) programmes initiated in Sweden, Denmark, the Netherlands and Finland. Many countries have also developed policies to promote healthy eating (Capacci et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Examples of national initiatives aiming for the adoption and maintenance of healthy lifestyle behaviours are physical activity programmes such as the “Exercise on Prescription” (Sørensen, Sørensen, Skovgaard, Bredahl, & Puggaard, 2011) and “Physical Activity on Prescription” (Olsson et al, 2015; Rödjer, Jonsdottir, & Börjesson, 2016) programmes initiated in Sweden, Denmark, the Netherlands and Finland. Many countries have also developed policies to promote healthy eating (Capacci et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Cultural differences in attitudes to foods are well recognised (25,26) , but accounting for differences between countries in our results is to some extent speculative as this was not explicitly explored by the questionnaire. It may, however, reflect national differences in policies and public health messages (27) . Lower prioritisation of the effect of food on mental performance indicates the potential for educating parents and building public awareness.…”
Section: Discussionmentioning
confidence: 99%
“…This review and another review of European nutrition policies (91) have found measures most frequently used by policies are those that allow consumers to make more informed choices. Apart from school food policies, strategies to improve the OH food environment are not nearly as well articulated or advocated.…”
Section: Discussionmentioning
confidence: 99%
“…It found that although OH food still remains excessive in energy, fat and Na, modest improvements were seen 18 months post implementation of menu labelling regulations (100) . Future evaluations may also consider responses that the consumer might make as a result of nutrition information, such as compensatory food choices at the dining occasion or in subsequent meals (91) .…”
Section: Discussionmentioning
confidence: 99%